2019
DOI: 10.3168/jds.2018-15652
|View full text |Cite
|
Sign up to set email alerts
|

Effects of milk replacer feeding rate and long-term antibiotic inclusion in milk replacer on performance and nutrient digestibility of Holstein dairy calves up to 4 months of age

Abstract: The objectives of this study were to evaluate calf performance and diet digestibility when feeding a milk replacer (MR; 25% crude protein, 18% fat, dry matter basis) at a moderate (MOD) and high (HI) rate, along with MOD with neomycin-oxytetracycline inclusion (1.43 each g/kg; NTMOD). Male Holstein calves (n = 48; 45 ± 1.0 kg of body weight; 3 to 4 d of age) were housed in individual pens for 56 d. All calves were initially fed 0.66 kg of dry matter from MR for the first p.m. and following a.m. feeding, then r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 53 publications
3
9
2
Order By: Relevance
“…Similar findings to the present study regarding MR feeding rate (LO vs. HI) and its effect on preweaning CS intake (Hill et al, 2016a;Dennis et al, 2018Dennis et al, , 2019, BW (Jasper and Weary, 2002;Khan et al, 2011;Rosenberger et al, 2017) and fiber apparent totaltract digestibility (Hill et al, 2016a;Dennis et al, 2018) have been reported. Feeding high rates of MR to calves should provide enough nutrients to sustain satiety largely on MR alone, thus decreasing CS intake compared with calves fed MR at a low rate, as was shown in the present study and previous reports (Hill et al, 2016a;Dennis et al, 2018Dennis et al, , 2019. The higher rate of MR feeding also resulted in higher BW until wk 7 from the greater ME intake compared with calves fed MR at a lower rate (Rosenberger et al, 2017).…”
Section: Effect Of Mr Feeding Ratesupporting
confidence: 91%
See 1 more Smart Citation
“…Similar findings to the present study regarding MR feeding rate (LO vs. HI) and its effect on preweaning CS intake (Hill et al, 2016a;Dennis et al, 2018Dennis et al, , 2019, BW (Jasper and Weary, 2002;Khan et al, 2011;Rosenberger et al, 2017) and fiber apparent totaltract digestibility (Hill et al, 2016a;Dennis et al, 2018) have been reported. Feeding high rates of MR to calves should provide enough nutrients to sustain satiety largely on MR alone, thus decreasing CS intake compared with calves fed MR at a low rate, as was shown in the present study and previous reports (Hill et al, 2016a;Dennis et al, 2018Dennis et al, , 2019. The higher rate of MR feeding also resulted in higher BW until wk 7 from the greater ME intake compared with calves fed MR at a lower rate (Rosenberger et al, 2017).…”
Section: Effect Of Mr Feeding Ratesupporting
confidence: 91%
“…In addition, MR has a higher digestibility compared with CS, therefore contributing more energy toward growth compared with CS. Studies reporting NDF and ADF digestibility have consistently noted that calves fed higher rates of MR have lower NDF and ADF digestibility at various weeks of life (Chapman et al, 2016;Dennis et al, 2018Dennis et al, , 2019. In our study, poor fiber apparent total-tract digestibility was carried over into the grower period (6 wk after weaning) by calves fed HI, as reported previously (Hill et al, 2016a).…”
Section: Effect Of Mr Feeding Ratesupporting
confidence: 84%
“…For calves fed MOD, MR was halved into a.m. and p.m. feedings for 35 to 39 d, followed by a.m. feeding of half of the previous MR amount for 3 to 7 d (Table 2). For calves fed HI, MR feeding regimens were more variable among the trials in 10 studies, of which there were constant (Hu et al, 2019), step-up (Hill et al, 2016a;Dennis et al, 2017Dennis et al, , 2018aDennis et al, , and 2019Quigley et al, 2018 and2019a), or step-up and step-down (Dennis et al, 2018b) MR feeding programs pre-weaning. In general, calves fed HI consumed equal amounts of MR twice daily (a.m. and p.m. feeding) for a period of 35 to 44 d, followed by a.m. feeding of half of the previous MR amount for 5 to 7 d (Table 2).…”
Section: Databasementioning
confidence: 99%
“…These results are consistent with Heinrichs et al (2003), who also found that neomycin, in combination with oxytetracycline, did not serve as promoters of frame size development, BW, or ADG. Dennis et al (2019) also found that a combination of neomycin and oxytetracycline in MR (1.43 g/kg of MR each, equivalent to 11.43-20.17 mg/ kg of BW per day each) for 42 d did not improve BW gain, although it did improve frame size development. However, Quigley et al (1997) found that oral administration of neomycin with oxytetracycline (2.7-3.3 mg/ kg of BW per day of neomycin and 1.3-1.7 mg/kg of BW per day of oxytetracycline for 26 d) in MR improved BW gain.…”
Section: Discussionmentioning
confidence: 92%
“…Some studies have shown that oral antimicrobials, including neomycin, are effective in reducing diarrhea occurrence in calves (Quigley et al, 1997;Heinrichs et al, 2003), and others associate oral antimicrobial usage with increased diarrhea incidence and severity (Shull and Frederick, 1978;Mero et al, 1985;Berge et al, 2009b). The effects of antimicrobial usage on growth performance variables are also conflicting, with one study showing improved calf growth (Quigley et al, 1997) and others showing no benefit (Heinrichs et al, 2003;Dennis et al, 2019). Several factors may contribute to these mixed results, including the use of different treatment antimicrobials, as well as varying dosages and durations used between studies.…”
Section: Introductionmentioning
confidence: 99%